2010
DOI: 10.1089/scd.2009.0483
|View full text |Cite
|
Sign up to set email alerts
|

Islet-1 Cells Are Cardiac Progenitors Present During the Entire Lifespan: From the Embryonic Stage to Adulthood

Abstract: The aim of this study was to longitudinally characterize the distribution of cells actively expressing the progenitor transcription factor islet-1 (Isl1+) during the embryonic life, the postnatal period, and adulthood. In this study, we have used direct immunohistochemical staining toward the protein Isl1 in a longitudinal rat model. Cells actively expressing Isl1 were traced in embryos from gestational day (GD) 11 until adulthood. In early cardiac development (GD 11), the Isl1+ progenitors were located in a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 27 publications
4
64
0
Order By: Relevance
“…Explant cultures revealed that ISL1 + cells can differentiate into cardiomyocytes and smooth muscle cells in vitro, and CRE lineage-tracing studies showed that ISL1 + progenitors contribute cardiomyocytes, endothelial cells and smooth muscle cells to the developing heart (Laugwitz et al, 2005;Moretti et al, 2006). Conditional CRE lineage-tracing studies in mice have revealed that immature ISL1 + cells persist beyond early heart development into fetal, neonatal and adult life, distributed in a pattern that is consistent with an SHF origin (Bu et al, 2009;Genead et al, 2010;Laugwitz et al, 2005), although this has not been formally proven. At fetal stages, some ISL1 + cells were negative for cardiac lineage markers (Bu et al, 2009), but most expressed the cardiomyocyte marker troponin T, suggesting a cardioblast identity, and only a minority were proliferating (Genead et al, 2010).…”
Section: Isl1 + Progenitor Cells Developmental Origins and Location Imentioning
confidence: 99%
See 1 more Smart Citation
“…Explant cultures revealed that ISL1 + cells can differentiate into cardiomyocytes and smooth muscle cells in vitro, and CRE lineage-tracing studies showed that ISL1 + progenitors contribute cardiomyocytes, endothelial cells and smooth muscle cells to the developing heart (Laugwitz et al, 2005;Moretti et al, 2006). Conditional CRE lineage-tracing studies in mice have revealed that immature ISL1 + cells persist beyond early heart development into fetal, neonatal and adult life, distributed in a pattern that is consistent with an SHF origin (Bu et al, 2009;Genead et al, 2010;Laugwitz et al, 2005), although this has not been formally proven. At fetal stages, some ISL1 + cells were negative for cardiac lineage markers (Bu et al, 2009), but most expressed the cardiomyocyte marker troponin T, suggesting a cardioblast identity, and only a minority were proliferating (Genead et al, 2010).…”
Section: Isl1 + Progenitor Cells Developmental Origins and Location Imentioning
confidence: 99%
“…Conditional CRE lineage-tracing studies in mice have revealed that immature ISL1 + cells persist beyond early heart development into fetal, neonatal and adult life, distributed in a pattern that is consistent with an SHF origin (Bu et al, 2009;Genead et al, 2010;Laugwitz et al, 2005), although this has not been formally proven. At fetal stages, some ISL1 + cells were negative for cardiac lineage markers (Bu et al, 2009), but most expressed the cardiomyocyte marker troponin T, suggesting a cardioblast identity, and only a minority were proliferating (Genead et al, 2010). Conditional lineage tagging of fetal ISL1 + cells showed that they do give rise to a minor proportion of cardiomyocytes in the postnatal murine heart (Laugwitz et al, 2005).…”
Section: Isl1 + Progenitor Cells Developmental Origins and Location Imentioning
confidence: 99%
“…However, aside from the Isl-1 pos CPCs which are direct progeny of a defined embryonic cardiac progenitor cell population present in only very small numbers in the adult heart 26 and the epicardial stem cells also called cCFU-Fs presumable derivate from the pro-epicardial organ 17 , it is evident just from the significant overlap of the main and secondary markers used for their characterization that the different eCSC/CPC populations are closely related. So it is not surprising that after the early enthusiasm subsided, a consensus is developing that many, if not all, different putative adult eCSCs reported so far, likely represent different developmental and/or physiological stages of a unique resident stemprogenitor cell type with multipotent regenerative capacity yet to be completely defined 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact interactions between senescence-related signalling pathways remain to be ascertained, theories have been proposed to explain the aging process, including theories of somatic mutation, mitochondrial DNA (mtDNA) mutation and telomere loss [123]. Furthermore, a variety of intrinsic and extrinsic systems are involved in the regulation of stem cell number and biological performance along with aging, such as cell-to-ECM, telomere-telomerase, growth factor-receptor, and ROS-antioxidant defence systems [122,124]. For instance, the IGF-1/IGF-1 receptor (IGF-1R) system preserves the pool of endogenous CSCs through enhancing telomerase activity and delaying senescence by activating the PI3K-Akt pathway, indicating that IGF-1 may protect CSCs against adverse aging effects [122].…”
Section: Effect Of Age On Isolation and Function Of Cardiac Stem Cellsmentioning
confidence: 99%
“…It has been shown that the IGF-1/ IGF-1R axis exists in cardiac stem cells in very old animals, but the IGF-1 synthesis and the IGF-1R expression are found to decrease in aging human CSCs [122,125,126]. In this regard, preconditioning of cultured resident CSCs in old age by over-expressing telomerase or up-regulation of favourable growth factor signalling may improve the regenerative capabilities of survival, growth and differentiation in vivo following transplantation [104,124,127]. Furthermore, in our group, hypoxic culture as a preconditioning treatment not only significantly increased cell yield but also enhanced telomerase levels and secretion of paracrine factors (e.g., VEGF and EPO) in rat CDCs (Tan et al in review).…”
Section: Effect Of Age On Isolation and Function Of Cardiac Stem Cellsmentioning
confidence: 99%